Efeito da toxicidade do alumínio sobre a resposta antioxidante endógena em três genótipos de aveia - Silva, Aniélen Dutra da (2016)
Aluminum (Al) is a metal that presents toxic effect on plant growth in acidic soils. In these soils, with pH under 5.5, Al can be found in its trivalent form (Al3+), which might compromise the root growth, as well as affect the plant physiological and biochemical processes. Cereal crops are highly affected by this toxicity, being Avena spp one of the most tolerant species to develop in acidic soils. Thus, the objective of this research was to evaluate and compare antioxidant system responses of three oat genotypes in vitro and verify if these parameters have an important participation on aluminum presence tolerance mechanism for each genotype. For this study, two commercial cultivars of oat (URS Charrua and URS Guria) and a known tolerant cultivar (UFRGS17) were selected through a program called Programa de Melhoramento de Aveia of Universidade Federal do Rio Grande do Sul (UFRGS). These genotypes were exposed to 740 μM of Al during five days and maintained in a growth room under controlled temperature and luminosity. The experiment consisted of six groups: UFRGS 17 control (CTL), URS Charrua CTL and URS Guria CTL were not exposed to Al; UFRGS 17 Al, URS Charrua Al and URS Guria Al were exposed to Al. Each group presents four replicates with eighty seedlings. After a period of five days, the plants were collected and separated in shoots and roots for the analysis of CAT, SOD, GPOX, pigment content, lipid peroxidation and H2O2 levels. Pigment concentration did not present changes in all genotypes, either in presence or lack of Al. However, CAT and SOD enzyme activities were reduced in Al presence and GPOX activity, presenting no changes in Al presence or absence. However, there was a reduction on CAT enzyme activity, on genotypes UFRGS 17 and URS in shoots and URS Charrua in roots. SOD enzyme presented a reduction on activity in UFRGS 17, URS Charrua e URS Guria shoots genotypes and URS Charrua e URS Guria in roots. On the other hand, GPOX enzyme was not suffered any changes with metal exposure. Lipid peroxidation and H2O2 levels had no alterations after the exposure to metal. GPOX could act maintaining H2O2 and lipid peroxidation levels, because its enzyme plays an important role in stress by metals when CAT, for example, has its activity reduced by metal toxicity. It is important to consider that genotypes responded in different forms to Al exposure, which demonstrates that tolerance mechanisms used for each genotype do not occur similarly. Moreover, other antioxidant system enzymes can be acting to control the oxidative stress, along with other mechanisms that can be acting under Al- toxicity.